Highly Biocompatible Functionalized Layer‐by‐Layer Ginger Lipid Nano Vectors Targeting P‐Selectin for Delivery of Doxorubicin to Treat Colon Cancer. Issue 12 (18th September 2019) - Zhang, Mingzhen; Yang, Chunhua; Yan, Xiangji; Sung, Junsik; Garg, Pallavi; Merlin, Didier
Abstract: A biocompatible natural nanoparticle drug delivery system that has specific cancer‐targeting function holds vast promise for cancer therapy. Here, a fucoidan/poly‐lysine‐functionalized layer‐by‐layer ginger‐derived lipid vector (LbL‐GDLV) is designed to target P‐selectin and deliver a loaded drug into vascularized colon cancer. LbL‐GDLVs selectively bound to P‐selectin, and the degradation of the fucoidan result in rapid attachment of the cancer cell and internalization of the remaining positively charged poly‐lysine coated‐GDLVs. Upon enzymolysis of the poly‐lysine layer inside the cancer cell, the GDLV core releases loaded doxorubicin (Dox) which has the expected effects. Bio‐distribution studies show that intravenously injected LbL‐GDLVs exhibit enhanced accumulation at the vascularized tumor site (≈4.4‐fold higher than control), presumably due to P‐selectin‐mediated targeting plus the enhanced permeability and retention effect (EPR). In two animal models (Luc‐HT‐29 and HCT‐116 xenografts), Dox‐loaded LbL‐GDLVs (LbL‐GDLVs/Dox) significantly inhibit tumor growth and demonstrate much better therapeutic efficiency than free Dox. More importantly, LbL‐GDLVs exhibit excellent biocompatibility, and LbL‐GDLVs encapsulation largely reduces the cardiotoxicity of free Dox and avoids the notorious drug resistance of colon cells against free Dox. Together, these findings demonstrate the potential of our newly designed and highly biocompatible plant‐derived LbL nanoparticles and their precise colon cancer drug delivery function. Abstract : A biocompatible natural nanoparticle drug delivery system that has specific cancer‐targeting function holds vast promise for cancer therapy. A fucoidan/poly‐lysine‐functionalized layer‐by‐layer ginger‐derived lipid vector (LbL‐GDLV) is designed to deliver loaded doxorubicin into vascularized colon cancer. LbL‐GDLVs exhibit excellent biocompatibility and LbL‐GDLVs encapsulation largely reduces the cardiotoxicity of free Dox and avoids the notorious drug resistance of colon cells.